2011
DOI: 10.1002/ange.201007671
|View full text |Cite
|
Sign up to set email alerts
|

Ein einheitlicher Ansatz zur stereoselektiven Totalsynthese von Pyridonalkaloiden und deren neuritogene Aktivität

Abstract: Ein Weg für alle: Die Entwicklung von Substanzen, die Neuritenwachstum induzieren, könnte ein wertvoller Ansatz zur Entdeckung potenzieller Medikamente gegen neurodegenerative Krankheiten sein. Mithilfe eines difunktionellen Bausteins gelang die Totalsynthese einer ganzen Reihe von entomopathogenen Pilzen produzierter Pyridonpolyen‐Naturstoffe, welche die Differenzierung von PC‐12‐Zellen verursachen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 58 publications
2
9
0
2
Order By: Relevance
“…The mixture was then warmed to room temperature, the solvent was removed under reduced pressure, and the residue was purified by silica gel column chromatography (petroleum ether/Et 2 O, 97:3) to give ester ( S )‐ 10 (776.6 mg, 67 %). The spectroscopic data for compound ( S )‐ 10 were identical to those described in the literature 8…”
Section: Methodssupporting
confidence: 55%
See 3 more Smart Citations
“…The mixture was then warmed to room temperature, the solvent was removed under reduced pressure, and the residue was purified by silica gel column chromatography (petroleum ether/Et 2 O, 97:3) to give ester ( S )‐ 10 (776.6 mg, 67 %). The spectroscopic data for compound ( S )‐ 10 were identical to those described in the literature 8…”
Section: Methodssupporting
confidence: 55%
“…in the presence of tetrapropylammonium perruthenate (TPAP; 0.03 equiv. ), in order to suppress the racemisation of the aldehyde intermediate, to produce (2 E ,4 S )‐ethyl 2,4‐dimethylhex‐2‐enoate [( S )‐ 10 ] in 67 % yield 8. Reduction of ( S )‐ 10 with DIBAL (diisobutylaluminum hydride) gave alcohol ( S )‐ 11 , whose subsequent oxidation with PCC (pyridinium chlorochromate) produced the corresponding aldehyde [i.e., ( S )‐ 9 ] 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[279] More recently, a divergent synthesis of various neurotrophic pyridone alkaloids was reported by Gademann and co-workers. [275d,280] The related farinosone C ( 290 ) [277] also promotes neurite outgrowth in NGF-mediated PC-12 cell lines at a concentration of 50 μM. [281] The authors reported a synthesis of 290 and have disclosed that L-tyrosinolamide represents its pharmacophore.…”
Section: Neurotrophic Natural Productsmentioning
confidence: 99%